Self-Emulsifying Granules and Pellets: Composition and Formation Mechanisms for Instant or Controlled Release - Ioannis Nikolakakis; Ioannis Partheniadis (MDPI AG, 2017)
Many articles have been published in the last two decades demonstrating improvement in the dissolution and absorption of low solubility drugs when formulated into self-emulsifying drug delivery systems (SEDDS). Several such pharmaceutical products have appeared in the market for medium dose (Neoral® for Cyclsoprin A, Kaletra® for Lopinavir and Ritonavir), or low dose medications (Rocaltrol® for Calcitriol and Avodart® for Dutasteride). However, these are in the form of viscous liquids or semisolid presentations, characterized by the disadvantages of high production cost, stability problems and the requirement of large quantities of surfactants. Solid SEDDS (S-SEDDS), as coarse powders, granules or pellets, besides solubility improvement, can be filled easily into capsules or processed into tablets providing a handy dosage form with instant release, which can be further developed into controlled release by mixing with suitable polymers or coating with polymeric films. In this review, the materials used for the preparation of S-SEDDS, their properties and role in the formulations are detailed. Factors affecting the physical characteristics, mechanical properties of S-SEDDS as well as their in vitro release and in vivo absorption are discussed. The mechanisms involved in the formation of instant and sustained release self-emulsifying granules or pellets are elucidated. Relationships are demonstrated between the characteristics of S-SEDDS units (size, shape, mechanical properties, re-emulsification ability, drug migration and drug release) and the properties of the submicron emulsions used as massing liquids, with the aim to further elucidate the formation mechanisms. The influence of the composition of the powdered ingredients forming the granule or pellet on the properties of S-SEDDS is also examined. Examples of formulations of S-SEDDS that have been reported in the literature in the last thirteen years (2004-2017) are presented.